# Finding the limit of a recursive sequence

Define the sequence $\{x_n\}_{n\in\mathbb{N}}$ by $$x_0=\frac{M}{2}, \qquad x_{n+1}=\frac{1}{2}\left(x_{n}+\frac{M}{x_{n}}\right)$$ where $M\in\mathbb{R}$, $M\geq 0$. Find $\lim\limits_{x_n\to\infty}x_{n}$ and prove it exists.

My idea was, if I can prove that $x_{n}\geq x_{n+1}$ then I can say that

$$x_{n}\geq x_{n+1}\iff x_{n}\geq\dfrac{1}{2}\left(x_{n}+\dfrac{M}{x_{n}}\right)\iff 2x_{n}\geq x_{n}+\dfrac{M}{x_{n}}\iff$$ $$x_{n}\geq\frac{M}{x_{n}}\Longleftrightarrow x_{n}^{2}\geq M\Longleftrightarrow x_{n}\geq\sqrt{M}$$

but I couldn't find a way to prove that $x_{n}\geq x_{n+1}$.

-
Do you want $x_0=M/2$ and $M\ge0$? –  David Mitra Jan 17 '12 at 22:06
i'm not sure about $x_0=n/2$. are you using $n$ in different ways? maybe you want $M/2$ or something else (besides zero)? –  yoyo Jan 17 '12 at 22:08
oops yeah, I mean M/2 –  sony jimbo Jan 17 '12 at 22:12
add comment

## 3 Answers

Assuming that $M>0$:

First we show that $(x_n)$ is bounded below:

Note $x_n$ satisfies $x_n^2-2x_{n+1}x_n+M=0$. This quadratic has a real root, so $4x_{n+1}^2-4M\ge 0$.

So $x_{n+1}^2\ge M$.

Next, we show that $(x_n)$ is eventually decreasing:

For $n\ge 2$ $$x_n-x_{n+1}=x_n-{1\over2}\Bigl(x_n+{M\over x_n}\Bigr)={1\over2}{x_n^2-M\over x_n}\ge 0$$

Thus, since $(x_n)$ is bounded below by $\sqrt M$ and is eventually decreasing, $(x_n)$ converges to some $L$ with $L\ge \sqrt M>0$. But then $$x_{n+1}\rightarrow{1\over2}\Bigl( L+{M\over L}\Bigr).$$

We then must have $$L={1\over2}\Bigl( L+{M\over L}\Bigr);$$ which implies $L=\sqrt M$.

If $M=0$, then $(x_n)$ obviously converges to 0.

-
+1: Interesting proof of $x_{n+1} \ge \sqrt{M}$. An easier proof (which generalizes to $k^{th}$ roots) uses $\text{AM} \ge \text{GM}$, see: math.stackexchange.com/questions/82682/… –  Aryabhata Feb 2 '12 at 2:02
add comment

For any positive $M$, this method seems to converge and is decreasing towards a solution after the first iteration (for $x_0 > 2$, it is always decreasing, but for $x_0 < 2$, it takes one iteration to increase and then decreases towards the solution. I'll explain that below). To have $x_n \ge x_{n+1}$, you need $$x_n \ge x_{n+1} = \frac 12 \left( x_n + \frac M{x_n} \right) \qquad \Longleftrightarrow \qquad x_n^2 - M \ge 0 \qquad \Longleftrightarrow \qquad x_n \ge \sqrt M$$ if we assume that $x_0$ is positive to begin with. (Otherwise, one can prove that a convergent sequence following this pattern will be a root of $x^2 - M$ with $M$ negative, which means that the root $x$ would be complex, which is not what you expect I assume). We show further that $x_n \ge x_{n+1} \ge M$. Now we can see that \begin{align} x_n^2 - 2 \sqrt M x_n + M = (x_n-\sqrt M)^2 \ge 0 \quad & \Longrightarrow \quad x_n + \frac{M}{x_n} \ge 2 \sqrt M \\ & \Longrightarrow \quad \frac 12 \left( x_n + \frac {M}{x_n} \right) \ge \sqrt M \\ \end{align} and therefore we know that after the first iteration, $x_n$ will always be above $\sqrt M$, since the only thing I assumed here was that $x_0$ was positive (strict).

Therefore the sequence is converging because it decreases and it is bounded below by $\sqrt M$. To find the limit, we have $$x_n \to L \qquad \Longrightarrow \qquad x_{n+1} \to L = \frac 12 \left( L + \frac ML \right) \qquad \Longrightarrow \qquad L = \sqrt M$$ by knowing the limit has to be positive (you'll find a quadratic with two roots in there).

To explain the first iteration thing, you have to note that $$x_0 = \frac M2 \ge \sqrt M \qquad \Longleftrightarrow \qquad (\sqrt M)^2 - 2 \sqrt M \ge 0$$ which in turn is equivalent to $\sqrt M \ge 2$, which means $M \ge 4$ and $x_0 \ge 2$. Hope that helps,

-
add comment

if the limit $x$ exists, then $x=(1/2)(x+M/x)$ and $x=\pm\sqrt{M}$. see newton's method applied to $f(x)=x^2-M$

-
sorry forgot to mention that we don't know if the limit xn exists –  sony jimbo Jan 17 '12 at 22:03
add comment